Ecological and economic assessment of agricultural products processing technologies - Moisienko, Maria; Kuznietsova, Olena; Garkava, Kateryna; Baranovskyy, Mikhaylo; Kosoholova, Liudmyla; Monchenko, Olena (Problems of Environmental Biotechnology, 2024)
An ecological and economic assessment of agricultural processing technologies was carried out.